Implementation of Deep Learning Approaches: Challenges and Solutions for Teachers: Implementasi Pendekatan Deep Learning: Tantangan dan Solusi Bagi Guru - Mukhoyaroh, Mukhoyaroh; Sodikin, Achmad; Waluyo, Waluyo (RADIANT: Journal of Applied, Social, and Education Studies, 2025)
Abstract This study aims to analyze the implementation of the deep learning approach and identify challenges and solutions in its application at Islamic Elementary Schools (Madrasah Ibtidaiyah) in Central Java Province. This study employs a descriptive qualitative approach. Data were collected through in-depth interviews, direct observation, and document analysis. The research subjects consist of teachers at Madrasah Ibtidaiyah located in the Central Java Province. The findings reveal that deep learning was implemented through three core elements:  1) mindful learning; 2) meaningful learning, and 3) joyful learning. However, teachers faced challenges such as: 1) The absence of instructional resources that facilitate deep learning; 2) Challenges in incorporating deep learning principles and formulating lesson plans, especially in organizing classroom activities and instructional materials suited to students' proficiency levels and requirements. Proposed solutions include: 1) Schools should be supported in creating and modifying relevant and practical teaching modules and 2) Facilitating specialized training for educators and learners on utilizing technology in education, encompassing the usage of online learning platforms. The study finds that the deep learning approach can be effectively utilized in the educational process to enhance students' innovative capabilities, collaborative preparedness, and capacity to address real-world situations.